E-government procurement implementation in India: evolving decision parameters for project success. (22nd July 2019) - Panda, Prabir; Sahu, G.P.; Gupta, Babita
Research indicates that India can save up to 25% in its public procurements (valued 3.4% to 5.7% of GDP) by migrating to e-government procurement (E-GP). This paper empirically studies stage-wise importance of 11 critical success factors (CSF) that were identified through extensive literature review. We developed a research model for ascertaining the impact of identified CSFs on various stages of E-GP which was fine-tuning after exploratory study. A survey of the stakeholders involved with E-GP system in India was conducted. We used regression analysis and mean score to empirically test the relationships identified between the CSFs and E-GP project success. The results show that five of the 11 CSFs are not important at stage 2 of E-GP project evolution, while all 11 CSFs contribute to the E-GP project success in stages 3 and 4. This study brings out India specific CSF based parameters for managerial decision making for E-GP project managers.